Women as editors-in-chief of environmental science journals - Yeverino Gutiérrez, Myrna Laura; González González, María del Rosario; Corral Symes, Ruth; González Santiago, Omar (UANL. Facultad de Ciencias Químicas, 2017)
This research note describes an analysis regarding the role of women as editors-in chief of environmental science journals. The list of journals analyzed was obtained from the database of “Web of Science”, published in 2015. This database does not include information on the name or gender of the editors-in-chief of journals, so a web search was performed. The results show that gender inequality is present in this important field of science. Causes of this bias merit more and profound research. The bias observed may not apply to journals of others areas of science.